2010
DOI: 10.3109/17453674.2010.533929
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent improvement in functional outcome following LCS rotating platform knee replacement

Abstract: Background and purposeLong-term follow-up studies after total knee replacement (TKR) using an LCS rotating platform have shown survival rates of up to 97%. Few studies have evaluated short-term functional outcome and its improvement over time. We determined the time course of functional outcome as evaluated by the knee injury and osteoarthritis outcome score (KOOS) over the first 4 years after TKR using the LCS mobile bearing.Patients and methods50 unselected patients (mean age 70 (40–85) years, 33 women) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…An increase in the maximal flexion at the mid-term follow-up was also observed in another CR study21), and a decrease in maximal flexion was observed in another PS study22). The change of flexion angle in the CR knee may be referable to a degeneration or failure of PCL.…”
Section: Discussionmentioning
confidence: 55%
“…An increase in the maximal flexion at the mid-term follow-up was also observed in another CR study21), and a decrease in maximal flexion was observed in another PS study22). The change of flexion angle in the CR knee may be referable to a degeneration or failure of PCL.…”
Section: Discussionmentioning
confidence: 55%
“…32 Previous studies comparing clinical outcomes of TKA longitudinally have suggested that further clinical improvement and recovery can take place beyond 6 months up to 2 years after surgery. 30,33,34 Our comparatively higher OKS are attributable to the fact that they were reviewed at a later follow-up interval of at least 2 years after surgery hence allowing for adequate time for maximal recovery and return to function. Altered kinematics and the resultant decrease in functional outcome in VVC knee implants, as compared with conventional primary TKA designs, have always been a concern owing to the increased constraint of the articulation.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective randomized study found no significant difference in functional outcome evaluated using WOMAC and SF-36 scores at 3-month and 1-year postoperative periods between the two groups4). As functional outcome measures were reported to improve up to 2 years of follow-up after TKA26,27), a difference in outcome at 2 years more comprehensively indicates the role of discharge destination. These results need to be communicated with patients, preoperatively, so that they can make informed decisions about their discharge destination.…”
Section: Discussionmentioning
confidence: 99%